Essential role of Her3 in two signaling transduction patterns: Her2/Her3 and MET/Her3 in proliferation of human gastric cancer. Issue 12 (14th November 2014) - Yun, Chen; Gang, Li; Rongmin, Gu; Xu, Wen; Xuezhi, Ming; Huanqiu, Chen
<x xml:space="preserve">Abstract</x> Various receptor tyrosine kinase (RTK) pathways were verified in many cancers including gastric cancer (GC), We sought to investigate the expression of RTKs including Her2, Her3, and Met and their transduction patterns in human GC. Over‐expression of Her2, Her3, and c‐Met in human GC was verified by immunohistochemistry leading to constitutive activation of RTK signaling pathways. Combined RTKs expression was valuable indicators for poor prognosis of GC patients. Using ErbB2 specific inhibitor Lapatinib and c‐Met specific inhibitor PHA‐665752, we further demonstrated that this constitutive activation of RTK signaling is necessary for the survival of GC cells. However, various RTK pattern: Her3/Her2 and Met/Her3 were verified in the transduction growth stimulus from outside via both AKT and MAPK signaling. Moreover, the essential roles of Her3 in both two heterodimers were obtained which showed significantly attenuated growth effect due to Her3 knockdown both in vitro and in vivo. In conclusion, various molecular transduction patterns: Her2/Her3 and Met/Her3 were verified in human GC, and Her3 could serve as a potential target in GC treatment. © 2014 Wiley Periodicals, Inc.